Transdisciplinary allied health assessment for patients with stroke: a pre-/post- mixed methods study protocol - Aleysha K. Martin; Theresa L. Green; Alexandra L. McCarthy; P. Marcin Sowa; E-Liisa Laakso (BMC, 2022)
Abstract Background Transdisciplinary approaches can streamline processes and build workforce capacity by blurring traditional responsibilities and integrating aspects of care. Emerging evidence shows transdisciplinary approaches can improve time-efficiency, quality of care and cost-effectiveness across various healthcare settings, however no empirical study is based on an acute stroke unit. Methods The SPIRIT checklist was used to guide the content of the research protocol. The study is a pragmatic pre−/post- mixed methods four-phase study with a 3-month follow up, based at the Mater Hospital Brisbane. Participants experiencing stroke symptoms will be recruited as they are admitted to the acute stroke unit. Patients presenting with mild stroke symptoms or Transient Ischaemic Attack will be allocated to Phase 1 (baseline) or Phase 2 (implementation), while patients presenting with moderate to severe stroke symptoms will be allocated to Phase 3 (baseline) or Phase 4 (implementation). Participants in baseline Phases 1 and 3 will receive standard allied health assessment, while participants in implementation Phases 2 and 4 will receive the novel transdisciplinary assessment. For the primary aim, allied health professionals will time their assessments to evaluate time taken to administer a novel transdisciplinary assessment, compared to usual discipline-specific assessments. Non-inferiority of the novel transdisciplinary assessment will also be explored in terms of patient safety, compliance to national standards, use of the assessment, and stakeholder perceptions. A retrospective medical record audit, staff focus group, patient/staff surveys, and patient phone interviews at 3-months will be completed. Quantitative results will be estimated using general linear and logistic regression models in Stata 15.1. Qualitative results will be analysed using frequency counts and NVivo software. An economic evaluation will be performed using three scopes including the allied health assessment, hospital admission, and patient outcomes at 3-months. Discussion When designing the study, pragmatic factors related to staff willingness to be involved, patient safety, and existing clinical pathways/processes were considered. To address those factors, a co-design approach was taken, resulting in staff buy-in, clinically relevant outcome measures, and the pre−/post- four-phase study design. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR), ACTRN12621000380897. Registered 06 April 2021 - retrospectively registered, https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=381339&isReview=true